2012
DOI: 10.1371/journal.pone.0044066
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoking Decreases Global MicroRNA Expression in Human Alveolar Macrophages

Abstract: Human alveolar macrophages are critical components of the innate immune system. Cigarette smoking-induced changes in alveolar macrophage gene expression are linked to reduced resistance to pulmonary infections and to the development of emphysema/COPD. We hypothesized that microRNAs (miRNAs) could control, in part, the unique messenger RNA (mRNA) expression profiles found in alveolar macrophages of cigarette smokers. Activation of macrophages with different stimuli in vitro leads to a diverse range of M1 (infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
106
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(115 citation statements)
references
References 63 publications
(101 reference statements)
7
106
2
Order By: Relevance
“…The same phenomenon was also observed in alveolar macrophages of smokers, where (57). In this later study the decrease in global miRNA expression was more pronounced in heavy smokers, suggesting that the magnitude of miRNA repression is related to the extent of smoking history (57).…”
Section: Mirnas Repression By Cigarette Smoke In the Lungssupporting
confidence: 79%
See 1 more Smart Citation
“…The same phenomenon was also observed in alveolar macrophages of smokers, where (57). In this later study the decrease in global miRNA expression was more pronounced in heavy smokers, suggesting that the magnitude of miRNA repression is related to the extent of smoking history (57).…”
Section: Mirnas Repression By Cigarette Smoke In the Lungssupporting
confidence: 79%
“…These results are supported by the study of Schembri et al, who found that most of the differentially expressed miRNAs in the human bronchial airway epithelium were downregulated in smokers and were inversely correlated with their predicted targets (56). The same phenomenon was also observed in alveolar macrophages of smokers, where (57). In this later study the decrease in global miRNA expression was more pronounced in heavy smokers, suggesting that the magnitude of miRNA repression is related to the extent of smoking history (57).…”
Section: Mirnas Repression By Cigarette Smoke In the Lungssupporting
confidence: 74%
“…Exposure to cigarette smoke caused down-regulation of some miRNAs in mouse and rat lungs (Izzotti et al, 2009a(Izzotti et al, , 2009b, and the down-regulation in mouse lung was reversed by smoking cessation (Izzotti et al, 2011). Similar findings have been reported in humans; the levels of several miRNAs in airway epithelium (Schembri et al, 2009), placenta (Maccani et al, 2010, and alveolar macrophages (Graff et al, 2012) were lower in smokers than in non-smokers. These results lead us to speculate that miRNAs in tissues, including trachea and lung, exposed to cigarette smoke might leak into blood.…”
Section: Discussionsupporting
confidence: 64%
“…To explore expression patterns at differentially methylated loci in the discovery cohort, we examined public data generated in airway and lung-related tissues available through the Gene Expression Omnibus (2,3,(20)(21)(22)(23)(24)(25)(26). Transcripts demonstrating nominally significant differences in expression (Student's t test P , 0.05) by current smoking status from selected studies are summarized in Table E8; at the majority of the loci examined, the direction of the expression changes were anticorrelated with the methylation changes observed in our analysis.…”
Section: Original Researchmentioning
confidence: 99%